Microsoft Windows Vista - Gary B. Shelly (Thomson Course Technology, 2008)
1. Fundamentals of Using Microsoft Windows Vista 2. Working on the Windows Vista Desktop 3. File and Folder Management Appendices A: Comparison of the New Features of Windows Vista Editions B: Windows Vista Security